Performance of the fullPIERS model in predicting adverse maternal outcomes in pre‐eclampsia using patient data from the PIERS (Pre‐eclampsia Integrated Estimate of RiSk) cohort, collected on admission. Issue 1 (19th October 2012) - Payne, B; Hodgson, S; Hutcheon, JA; Joseph, KS; Li, J; Lee, T; Magee, LA; Qu, Z; von Dadelszen, P; ,
<x xml:space="preserve">Abstract</x> The fullPIERS (Pre‐eclampsia Integrated Estimate of RiSk) model is a promising tool for the prediction of adverse outcomes in pre‐eclampsia, developed using the worst values for predictor variables measured within 48 hours of admission. We reassessed the performance of fullPIERS using predictor variables obtained within 6 and 24 hours of admission, and found that the stratification capacity, calibration ability, and classification accuracy of the model remained high. The fullPIERS model is accurate as a rule‐in test for adverse maternal outcome, with a likelihood ratio of 14.8 (95% CI 9.1–24.1) or 17.5 (95% CI 11.7–26.3) based on 6‐ and 24‐hour data, respectively, for the women identified to be at highest risk (predicted probability ≥30%).